Development of a kpi monitoring system for on-line assessment of USM'S APEX status. - Kien, Phua Kia (Pusat Pengajian Kesihatan, 2015)
The Key-Performance Indicator Monitoring System (KPI-MS) is an online computer system developed for PT Js in USM to store their KPI data, calculates total KPI marks and generates reports and charts for assessment of KPI achievements. This system is currently hosted at http:/110.202.1.63/usmkpims to enable online interaction between Bahagian Pembangunan Lestari & Korporat (BPLK) and PT Js. This system is designed to replace the current RU Questionnaire Excel spreadsheet system which has several short comings. The KPI-MS offers a more secure and efficient system for management of KPI data and for interacting with BPLK for the overall monitoring of USM KPI performance .